Omega-3 supplementation, milk quality and cow immune-competence - Andrea Bragaglio; Ada Braghieri; Fabio Napolitano; Giuseppe De Rosa; Amelia Maria Riviezzi; Francesca Surianello; Corrado Pacelli (Italian Journal of Agronomy, 2015)
This study aimed to assess the effect of a dietary supplementation rich in n-3 fatty acids from algae (Schizochytrium sp.) on cow immune-competence and milk quality. Twenty-one lactating Italian Friesian cows (at 220±20 days of lactation) were equally allocated to 3 treatments: group C received no supplementation, group D was offered 136 g of docosahexaenoic acid (DHA) per day and group E was supplemented with 136 g of DHA + 2000 U.I. of vitamin E per day. Individual milk production was recorded weekly and samples were collected for analysis of milk composition and fatty acid profile. At the end of the trial and 2 weeks later animals were subcutaneously injected with 5 mg of keyhole limpet haemocyanin (KLH), whereas at the end of the trial and 8 weeks later skinfold thickness was measured after intradermal injection with 500 mg phytohaemagglutinin. Dietary treatment showed no effect on milk production. Concentrations of DHA were higher (P<0.05) in milk fat from D and E groups, whereas polyunsaturated fatty acids tended to be higher (P<0.10). When DHA and DHA + vitamin E were supplemented to the animals, milk sensory properties were significantly modified as samples from groups D and E could be discriminated from the control using the triangle test (P<0.001). Both supplemented groups showed evidence of increased antibody response 4 to 8 weeks after the first KLH administration (P<0.05). In the two skin tests the treated groups showed a higher skin thickening in comparison with control animals (P<0.05). Although provided in a late stage of lactation, an n-3 fatty acid enriched diet favourably changed milk fatty acid profile and promoted animal healthiness by enhancing cellular and humoral immune response.